Comparative analysis of framing and journalistic role performance in energy news in mainstream and business media from 2020–2024 - Acabal, Isa Jane D.; Millenas, Janna Grace
The Philippines is currently facing an energy crisis amid depleting resources and increasing demand. With their central role in shaping public discourse, journalists are then expected to report relevant and science-based energy stories to inform the public. However, literature found that energy reporting focused on business and political themes, steering away from scientific and environmental angles. Along this, studies on journalistic roles mainly focused on perceived ideals instead of their actual manifestation in journalistic outputs. Guided by Claes de Vreese framing model and Claudia Mellado’s professional roles framework, this study conducted a content analysis of 1,008 articles to analyze the framing and presence of journalistic role performance (JRP) in energy news in online mainstream and business media. Results showed that economic and political frames significantly dominated energy reportage, leaving out environmental, civil society, and sci tech frames. Concurrently, business and government officials were the most cited sources while ordinary citizens came in last, suggesting lack of public representation in energy issues. This finding revealed the need to diversify sources and highlight inherent environmental and scientific frames. Still, as JRP results showed, journalists performed important functions as disseminator-interventionists, civic, and watchdogs in energy reporting.